Human mental workload : models and applications : second International Symposium, H-WORKLOAD 2018, Amsterdam, The Netherlands, September 20-21, 2018, Revised selected papers /: models and applications : second International Symposium, H-WORKLOAD 2018, Amsterdam, The Netherlands, September 20-21, 2018, Revised selected papers. (2019) - Unknown
No abstract available